Total Lactic Acid, Protein, Fat, and Carbohydrates in Curd Kefir and Cow Colostrum Kefir - Tuti Kurniati; Neneng Windayani; Milla Listiawati (UIN Sunan Gunung Djati Bandung, 2020)
There are differences in the content of lactic acid, fat, pro-tein and carbohydrates in the curd kefir and colostrum kefir. The aims of this study were to determine the content of lactic acid, protein, fat, and carbohydrates of curd kefir and colostrum kefir based on the con-centration of starter and fermentation time. Experimental data were collected from a number of experiments at a temperature of 28°C. The method used was the experimental method of CRD 3 × 3 with 3 replications, the data were analyzed by analysis of variance. Good kefir contained high lactic acid, proteins, and carbohydrate and low in fat. The results showed curd kefir with the highest lactic acid con-tent of 1.59 % was at a starter concentration of 20% and a fermen-tation time of 72 hours (d2w3), the highest protein of 2.20% was at a starter concentration of 30% and a fermentation time of 72 hours (d3w3), the lowest fat of 1.16% found at a starter concentration of 30% and a fermentation time of 72 hours (d3w3), and the highest carbohydrate of 4.81% found at a starter concentration of 30% and a fermentation time of 72 hours (d3w3). Whereas in colostrum ke-fir with the highest lactic acid content of 2.83 % found at a starter concentration of 20% and a fermentation time of 72 hours (d2w3), the highest protein of 6.13 % was at a starter concentration of 10% and a fermentation time of 24 hours (d1w1), the lowest fat of 1.58% was at a starter concentration of 30% and fermentation time of 24 hours (d3w1) and the highest carbohydrate content of 17.91% was at a starter concentration of 30% and a fermentation time of 72 hours (d3w3). It can be concluded that the starter concentration and fer-mentation time have a significant effect (α <0.05) on lactic acid, pro-tein, fat, and carbohydrates content of curd kefir and kefir colostrum.